The Effect of GoTo (Gojek X Tokopedia) Internet Advertising and Electronic Word of Mouth (Ewom) on Purchase Decisions (Case Study on Consumers Who Use Courier Services) - Andhi Sukma; Feby Febriana Dery (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Since the presence of the pandemic, there has been a shift where consumers are now more inclined to make transactions or shop online rather than shopping at conventional stores. Besides that, brand awareness of local products presented through social media can also influence buying interest. So that throughout 2021, public interest in local brands has increased significantly since the COVID-19 pandemic began, including in the city of Bandung. The research method that the authors implement in this study is a type of quantitative research aimed at analyzing a particular sample or population as well as descriptive research. The researcher used primary data in the form of the results of a questionnaire conducted on 100 respondents, which included the millennial generation with an age range of 13-30 years and secondary data, namely processed data that already existed such as journals, books, articles and other sources. The aim is to find out the effect of digital marketing and brand awareness on purchasing decisions for local Umkm fashion brands in post-new normal Bandung city. The results of this study found that there was an influence of digital marketing and brand awareness on purchasing decisions. Keywords: Brand Awareness, Digital Marketing, Local Brand, Purchase Decision.